Supported copper triflate as an efficient catalytic system for the synthesis of highly functionalized 2-naphthol Mannich bases under solvent free condition - Dindulkar, Someshwar D.; Puranik, Vedavati G.; Jeong, Yeon Tae (Tetrahedron Letters, 2012)
Various heterogeneous catalysts (Lewis acid) have been prepared and screened for the synthesis of Betti bases in an attempt to reduce the environmental hazards associated with the conventional homogeneous Lewis acid system. And we found especially Cu(OTf)(2)center dot SiO2 catalyzes the three-component coupling of aldehyde, 2-naphthol, and alicyclic amine to generate Betti base with high efficiency under neat conditions without additional co-catalyst or additive in air. The reaction is not sensitive to water and occurs smoothly in water as well. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Betti bases; single-crystal XRD; Solvent-free; Supported copper triflate; Three-component coupling

Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one

Synthesis of diverse nitrogen fused polycyclic dihydroisoquinoline (DHIQ) derivatives via GBB-based cyclic iminium induced double-annulation cascade - Balwe, Sandip Gangadhar; Vagh, Sandip S.; Jeong, Yeon Tae (Tetrahedron Letters, 2020)
A highly efficient and distinct Bronsted acid-mediated unprecedented cyclic iminium induced double annulation cascade (DAC) protocol for the synthesis of novel dihydroindazolo[30,20:2,3]imidazo[5,1-a]isoquinolinamines has been achieved through the three-component Groebke-Blackburn-Bienayme reaction. The transformation is based on sequential cascade processes involving imine formation followed by an intramolecular nucleophilic substitution to generate a highly reactive cyclic iminium species, which would undergo a rapid [4 + 1] formal cycloaddition steps in one-pot fashion. This strategy provides novel skeletally diverse complex nitrogen fused polycyclic DHIQ derivatives by employing readily available substrates and a simple procedure, which would render this method potentially useful in organic synthesis. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: diversity-oriented synthesis; Excellent yields; GBB-based approach; Novel polycyclic N-fused architecture; Scalable